Necrotizing soft tissue infection at an uncommon site following tooth extraction - R., Raksha; S., Varsha; Rajagopalan, S. (International Surgery Journal, 2019)
Necrotizing soft tissue infection (NSTI) is a disease characterized by rapidly progressive necrosis involving skin, subcutaneous tissue, fascia or muscle. It is commonly seen in extremities, perineum and lower abdomen. It is extremely uncommon for necrotizing fasciitis to occur along the chest wall, with only a few such cases being reported. We report one such rare case of NSTI in a 75 year old male who underwent left molar tooth extraction developed Ludwig’s angina which progressed to present as a painful swelling over the left side of the neck and chest with a necrotic patch of skin over manubrium sternum managed successfully.